Comparative Efficacy of Botulinum Toxin in Salivary Glands vs. Oromotor Therapy in the Management of Sialorrhea in Cerebral Palsy Impact on Sleep Quality - Marquez-Vazquez, Juan Francisco; Arellano-Saldaña, María Elena; Rojas-Martinez, Karla Nayeli; Carrillo-Mora, Paul (Frontiers in Rehabilitation Sciences, 2022)
Aims: The aim of this study was to compare the effects of intraglandular abobotuliniumtoxinA application and oromotor therapy in the management of sialorrhea in patients with cerebral palsy and its effect on sleep quality. Methods: A comparative study (n=134), mean age 7.1 years (± 3.9 years) was performed in pediatric patients, between the efficacy of abobotuliniumtoxinA in salivary glands and oromotor therapy (JT), with a control group receiving Exclusive Oromotor Therapy (EOMT). Demographic variables, as well as GMFCS, DSFS, SDSC and EDACS were analysed in 134 patients considering two measurements six months apart. Statistical analysis was developed between both groups. Results: The greatest improvement in safety and efficacy of swallowing were those in the JT group with initial levels of EDACS IV and V. Both therapies result in favourable changes of all subscales means of SDSC, with joint therapy showing the greater benefit (p=0.003) over EOMT (p=0.06), especially for Sleep Breathing Disorders and Disorders of initiating and maintaining sleep (p<0.01 versus p=0.07). No major adverse effects were found, only those expected from the application of the toxin, such as pain, mild and transient local inflammation Interpretation: A correlation between frequency and intensity of sialorrhea, with the frequency of sleep disorders and dysphagia was found. Conventional EOMT proved to be useful, improving the safety and efficacy of swallowing, sialorrhea and sleep disorder, however it can be enhanced with the application of abobotuliniumtoxinA.